ENTREPRENEURIAL ORIENTATION TOWARDS BUSINESS PERFORMANCE THROUGH BUSINESS STRATEGY WITH ENVIRONMENTAL DYNAMICS AND GOVERNMENT POLICY AS MODERATING VARIABLES - Prajawati, Maretha Ika; Aisyah, Esy Nur; Yuliati, Yuliati; Al Idrus, Salim (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study aims to examine the influence of entrepreneurial orientation on business strategy and organizational performance among halal small and medium enterprises (SMEs) in Malang City. It further investigates the mediating role of business strategy and the moderating effects of environmental dynamics and government policies. Using a quantitative research design, data were collected from halal SMEs in the food and beverage sector through a non-probability (accidental) sampling technique. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed to test the proposed hypotheses. The findings reveal that entrepreneurial orientation significantly affects both business strategy and firm performance. Business strategy mediates the relationship between entrepreneurial orientation and performance, while environmental dynamics do not significantly moderate the effect of strategy on performance. However, government policies strengthen the influence of entrepreneurial orientation on the performance of halal enterprises. The results highlight that a strong entrepreneurial mindset, supported by conducive government policies, can enhance the productivity and competitiveness of halal SMEs operating in creative economy sectors. JEL: H2, M2, M5.